Relevance of Staff Development in School Administration in Selected Senior Secondary Schools - Olawale Abayomi Onikoyi (Indonesian Journal of Multidiciplinary Research, 2023)
The efficient and effective performance of the workforce, in turn, rests on the richness of the knowledge, skills, and abilities possessed by the workforce. Staff development both physically, socially, intellectually, and mentally is very essential in facilitating not only the level of productivity but also the development of personnel in any organization the study investigates the relevance of staff development in school administration in Education District VI, Lagos State. The study aimed to examine the relationship between satisfaction with in-service training, mentoring, workshop/seminar, principal attendance at conferences, and school administration in Education District VI, Lagos State. Five research questions were answered and five hypotheses were tested. The descriptive survey research design was adopted for the study. The sample size of the study comprised 308 teachers selected from 12 public secondaries in Education District VI of Lagos State using a stratified random sampling technique. The research instrument adopted for this study was a self-structured questionnaire which was tagged â€œStaff Development and School Administration Questionnaire (EATJPQ)â€ It was designed using the four-point Likert Scale type. Data collected were analyzed using descriptive statistics of percentage to analyze participantsâ€™ bio-data and percentage and mean were used to answer the research questions, while Pearson Product Moment Correlation and regression statistical tools were used to test the hypotheses.